Comportamento mecânico do aço AISI 41B30 na deformação a quente - Túlio César Nogueira (2021)
High pressure gas cylinders (gas cylinders) are manufactured from the rolling of special seamless steel tubes. The efforts required during the rolling step are directly dependent on the chemical composition of steels, strains, strain rates and temperature in the rolling mill. These parameters are used to carry out the rolling simulations in laboratory in order to know the resulting substructures and microstructures of the process. The objective of this work is to evaluate the softening mechanisms that occur in a AISI 41B30 steel at temperatures of 950°C, 975°C, 1000°C 1025°C and 1050°C, using the strain rates of 10s-1, 20s-1, 30s-1 and 40s-1 and true strain of 1.5, when performing plane strain compression tests on thermomechanical simulator Gleeble® 3800. The temperature ranges and strain rates were chosen because they were the same as those included in the schedule of the Premium Quality Finishing (PQF) industrial mill of Vallourec Soluções Tubulares do Brasil. To study the softening mechanisms of after the compression tests, true stress versus true strain curves were constructed to understand the processes in each case. Microstructural characterization was executed in the quenched samples after the total strain of 1.5, by Scanning Electron Microscopy (SEM) to establish the medium diameter of the prior austenite grains. The results of this work show the softening mechanisms, the constitutive equation and the evolution of the prior austenite grain size for the AISI 41B30 steel as function of the different conditions of thermomechanical processing. The predominance of the dynamic recrystallization mechanism in all conditions is observed, a constitutive equation is shown with good correlation to predict stress levels for the process. It was also observed that the refining of prior austenite grain occurs with the increase of the strain rate and reduction of temperature.